Il cotile a doppia mobilità: una nuova rivoluzione nell’artroprotesi d’anca - Caton, J.; Amendola, L.; Castiello, E.; Comitini, S.; Tigani, D. (Lo Scalpello - Journal, 2019)
DUAL MOBILITY CUP: A NEWTHA REVOLUTION Dislocation following Total Hip Arthroplasty (THA) remains the leading reason for revision in the first 2 years. Dual mobility cup (DMC) was developed in France in the early seventies by G. Bousquet and his engineer A. Rambert with the aim of reducing dislocation rate in THA, representing also an alternative to large femoral head. Based on our clinical results and the current literature, DMC is a reliable surgical procedure. In France the dislocation rate has globally decreased from 9.06% in 2005 to 6.10% in 2014. In the field of THA, the DMC may be considered as the second “French revolution”.